PENGEMBANGAN LEAFLET BERBASIS SQ3R PADA MATERI HIDROKARBON KELAS XI IPA MA AL-MUSTAQIM - Wachidah, Nur; Sahputra, Rachmat; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract The aims of research were to determine the feasibility and readability of SQ3R-based leaflets on hydrocarbon material. This research takes the form of research and development (R&D) which adopts the Borg & Gall development model. The subjects of this study were students of class XI IPA MA Al-Mustaqim. Data collection techniques using measurement techniques, indirect communication techniques, and direct communication techniques. The assessment instrument was in the form of a feasibility assessment sheet filled out by experts, a student questionnaire response sheet, and an unstructured interview draft. The results of data analysis showed that the SQ3R-based leaflet on hydrocarbon material was very feasible (87%), including of content (92%), presentation (90%), lingustic (79%), and graphic aspect (87%P. Based on students response questionnaire in trial I, the result was 83% and in trial II the result was 81%. This data showed that students' response to the SQ3R-based leaflet on hydrocarbon material is included in the very good category. Keywords: Development, Hydrocarbons, SQ3R-Based Leaflets T